Impact of abiraterone acetate plus prednisone in patients with castration-sensitive prostate cancer and visceral metastases over four years of follow-up: A post-hoc exploratory analysis of the LATITUDE study. (February 2022) - Baciarello, Giulia; Özgüroğlu, Mustafa; Mundle, Suneel; Leitz, Gerhard; Richarz, Ute; Hu, Peter; Feyerabend, Susan; Matsubara, Nobuaki; Chi, Kim N.; Fizazi, Karim
Abstract: Background: A post-hoc analysis of the phase-3 LATITUDE study assessed the impact of abiraterone acetate plus prednisone (AA+P) on overall survival (OS) and radiographic progression-free survival (rPFS) in men with metastatic castration-sensitive prostate cancer (mCSPC) and visceral metastases (VM). Methods: Newly diagnosed mCSPC patients were randomized (1:1) to AA+P and androgen deprivation therapy (ADT) or placebo+ADT. Patients with VM in liver or lungs with or without other soft tissue and bone metastases (based on CT/MRI) at baseline were analyzed, after 51.8 months' median follow-up. Co-primary endpoints, OS and rPFS, were analyzed. Results: Among 1199 patients enrolled, 228 (19%) had VM at baseline (114 each in AA+P and placebo groups), of which 53 (23.2%; AA+P = 29, Placebo = 24) had liver metastases and 117 (51.3%; AA+P = 60, Placebo = 57) had lung metastases. In patients with VM, treatment with AA+P versus placebo showed an improvement in OS (median 55.4 vs 33.0 months; HR = 0.582; 95%CI = 0.406–0.835; P  = 0.0029) and rPFS (median 30.7 vs 18.3 months; HR = 0.527; 95%CI = 0.366–0.759; P  = 0.0005), comparable to that of patients without VM. AA+P versus placebo in lung metastases patients was associated with greater improvement in OS (HR = 0.60; 95%CI = 0.35–1.04; P  = 0.0678) than in liver metastases patients (HR = 0.82; 95%CI = 0.41–1.66; P  = 0.5814). AA+P versus placebo showed improvement in rPFS in lung metastases patients (HR = 0.50; 95%CI = 0.29–0.89; P  = 0.0157), but not in liver metastases patients (HR = 1.05; 95%CI = 0.53–2.09; P  = 0.8970). Conclusion: AA+P treatment improved both rPFS and OS in men with mCSPC and visceral disease, especially those with lung metastases. Men with liver metastases had a poorer prognosis and their optimal treatment remains to be defined. Registration: ClinicalTrials.gov, number NCT01715285 Highlights: AAP+ADT showed survival benefit in mCSPC men regardless of visceral disease status. Men with liver metastases had a poorer prognosis than those with lung metastases. A benefit in OS and rPFS was not seen in the small group of men with liver metastases.